The Prospects of Digital Gold Investment Among Generation Z: A Perception Analysis Based on a Modified UTAUT Model - Lina Wati; Rama Dani (Journal of Innovative and Creativity, 2026)
The rapid development of financial technology has led to the emergence of various digital investment instruments, including digital gold investment, which has gained increasing popularity among Generation Z. Nevertheless, the adoption of this instrument remains influenced by users’ perceptions of its benefits, ease of use, and social legitimacy. This study aims to examine Generation Z’s perceptions of digital gold investment prospects by employing a modified Unified Theory of Acceptance and Use of Technology (UTAUT) framework, incorporating performance expectancy, effort expectancy, and social influence. This study adopts a quantitative approach using a survey method involving 100 Generation Z respondents in Medan City. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings reveal that performance expectancy, effort expectancy, and social influence have a positive and significant effect on Generation Z’s perceptions of digital gold investment prospects. Among these factors, performance expectancy emerges as the most dominant determinant, followed by social influence and effort expectancy. These results suggest that Generation Z is more likely to perceive digital gold investment favorably when it is viewed as economically beneficial, easy to use, and socially endorsed. This study contributes theoretically by extending the application of the UTAUT model within the digital investment context and provides practical implications for digital gold investment.